A Review of Research on the Effects of Psychological Emotions on Cooperative Innovation Contexts - Zhao, Tongyue (International Journal of Global Economics and Management, 2024)
Under the double influence of the anti-globalisation trend and the impact of the new crown epidemic, enterprises have gradually found that evaluating innovation performance solely from objective factors such as performance and network status is monotonous and one-sided. Enterprises are a huge and complex whole composed of countless individuals, and individual subjective emotions such as incentives, moods, and experiences also affect the innovation results of enterprises to a certain extent. Therefore, by introducing the factor of psychological emotion into the context of enterprise cooperation and innovation, this paper summarises the research related to psychological emotion of innovation and explores the conceptual connotation, dimension division, and variable measurement of psychological emotion of innovation, with a view to expanding the theoretical derivation of the influence of psychological emotion on enterprise innovation and helping enterprises to achieve innovation and high-quality development.